2021
DOI: 10.7717/peerj.10851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leaf position and days post-infiltration on transient expression of colorectal cancer vaccine candidate proteins GA733-Fc and GA733-FcK in Nicotiana benthamiana plant

Abstract: Immunization with thetumor-associated antigen GA733 glycoprotein, which is highly expressed in colorectal cancer, is considered to be a promising strategy for cancer prevention and treatment. We cloned a fusion gene of GA733 and immunoglobulin Fc fragment (GA733-Fc), and that of GA733-Fc and an endoplasmic reticulum retention motif (GA733-FcK) into the Cowpea mosaic virus (CPMV)-based transient plant expression vector, pEAQ-HT. Agrobacterium tumefaciens (LBA4404) transformed with the vectors pEAQ-HT-GA733-Fc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous studies demonstrated that too low cell density might lead to insufficient Agrobacterium infection, whereas too high density may cause necrosis (Kagale et al, 2012 ; Leuzinger et al, 2013 ; Yan et al, 2019 ). Additionally, the harvesting time also affects the necrosis and amount of protein production (Kim et al, 2021 ). Our work revealed that the Agrobacterium cell density (OD 600 ) of 0.5 and the harvest time of 7 dpi were the optimal conditions for GCase transient production, as they resulted in the highest GCase enzyme activity in both WT and ΔgntI-infiltrated leaves ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that too low cell density might lead to insufficient Agrobacterium infection, whereas too high density may cause necrosis (Kagale et al, 2012 ; Leuzinger et al, 2013 ; Yan et al, 2019 ). Additionally, the harvesting time also affects the necrosis and amount of protein production (Kim et al, 2021 ). Our work revealed that the Agrobacterium cell density (OD 600 ) of 0.5 and the harvest time of 7 dpi were the optimal conditions for GCase transient production, as they resulted in the highest GCase enzyme activity in both WT and ΔgntI-infiltrated leaves ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of recombinant PAP-IgM FcK × J-chain Purification of recombinant PAP-IgM FcK × J-chain protein from transgenic plant leaves protein from transgenic plant leaves Recombinant PAP-IgM FcK × J-chain fusion protein was purified according to a previous study (Kim et al, 2021;Lim et al, 2022). Briefly, the homogenized plant leaves of extraction buffer were centrifuged at 8,800 ×g for 30 min at 4℃.…”
Section: Immunoblot Analysis Immunoblot Analysismentioning
confidence: 99%
“…After the saturated suspension was incubated for overnight at 4℃. The suspension was centrifuged at 8,800 ×g for 30 min at 4℃, the pellet was resuspended in 1× PBS to 1/10 of the previous volume, and the final suspension was then centrifuged at 10,200 ×g for 30 min at 4℃ (Kim et al, 2021;Lim et al, 2022). The supernatant was then filtered through a hydrophilic PVDF 0.45 μm filter (Millipore, Billerica, MA).…”
Section: Immunoblot Analysis Immunoblot Analysismentioning
confidence: 99%
“…Finally, an interesting biotechnological application of KDELR-mediated retention within the ER is the preparation of anticancer immunogens and, more generally, the production of recombinant proteins. The inclusion of a KDEL sequence increases both the production and quality of recombinant proteins prepared for therapeutic purposes in plant systems, as reported for the epithelial cell adhesion molecule (EpCAM), one of the tumor-associated antigens [ 109 , 110 , 111 ]. It has been proposed that the introduction of a KDEL sequence, by retaining KDEL-labeled proteins in the ER, avoids the attachment of complex glycans that could eventually trigger allergic responses in treated patients [ 111 ].…”
Section: Kdelrs Are Possible Targets In the Treatment Of Diseases To ...mentioning
confidence: 99%